Efficacy of pregabalin premedication prior to surgery in attenuating the adverse hemodynamic response to laryngoscopy and tracheal intubation - Reddy, M. Srinivas; Murari, Nagaratna (International Journal of Advances in Medicine, 2019)
Background: In general pregabalin is used in patients with normal blood pressure undergoing operation for controlling the response of the pressor in nature. There are few studies which have been carried out to study efficacy of pregabalin in controlling responses to instrumentation of the airway in patients with controlled hypertension. Objective was to study efficacy of pregabalin premedication 90min prior to surgery in attenuating the adverse hemodynamic response to laryngoscopy and tracheal intubation. Methods: Hospital based randomized comparative trial was conducted. 100 patients of ASA I and II physical status aged 18-60 yrs scheduled to undergo elective surgery like orthopaedic, spine, otorhinolaryngeal, gynaecological and general surgical procedures. Patients were randomly divided into 2 groups of 50 each. Randomization was done by computer generated table. Group "P" received- 150mg pregabalin. Group "C" received-200µg clonidine. Results: The patients in clonidine group documented the heart rate as more compared to the patients in the pregabalin group at various time intervals. The patients in clonidine group documented the mean systolic blood pressure as more compared to the patients in the pregabalin group at various time intervals. The patients in clonidine group documented the mean diastolic blood pressure as more compared to the patients in the pregabalin group at various time intervals. Conclusions: We concluded that use of pregabalin is more effective in comparison to use of clonidine in terms of controlling the hemodynamic parameters. But it has been found that bradycardia may not be properly attenuated with the use of pregabalin.